1995
DOI: 10.1063/1.360603
|View full text |Cite
|
Sign up to set email alerts
|

The composition of octahedron structures that act as an origin of defects in thermal SiO2 on Czochralski silicon

Abstract: Recently, octahedron structures have been found in the Czochralski-silicon substrate surface layer just under the oxide defects. An attempt is made to characterize these structures by analysis with transmission electron microscopy and energy-dispersive x-ray spectroscopy. Several results indicate that the structure is full of vacancies. This is contrary to previously reported results suggesting that the octahedron structures found in Si bulk are filled with amorphous SiO2. A model for the formation of an octah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(77 citation statements)
references
References 15 publications
2
75
0
Order By: Relevance
“…Voids have been observed directly by TEM to organize into octahedral structures aligned almost exclusively along the (111) crystallographic planes of the silicon lattice 25 . This phenomenon has been explained by the low energy of the Si (111) surface relative to other orientations 26 , and an important goal of this work is to make a detailed connection between the thermodynamics of small vacancy clusters and large octahedral voids.…”
Section: Vacancy Aggregation In Crystalline Siliconmentioning
confidence: 99%
“…Voids have been observed directly by TEM to organize into octahedral structures aligned almost exclusively along the (111) crystallographic planes of the silicon lattice 25 . This phenomenon has been explained by the low energy of the Si (111) surface relative to other orientations 26 , and an important goal of this work is to make a detailed connection between the thermodynamics of small vacancy clusters and large octahedral voids.…”
Section: Vacancy Aggregation In Crystalline Siliconmentioning
confidence: 99%
“…The facets are aligned along ͑111͒ orientations as observed experimentally for much larger voids found in Czochralski silicon crystals after cooling. 8 In other words, these structures are close to their expected energetic ground states.…”
Section: Cluster Morphologies and The Effect Of Entropymentioning
confidence: 99%
“…This particular system choice is based on the fact that vacancy aggregation is a technologically important pro-cess that has been characterized in detail with experiments 8,9 and detailed continuum models, [10][11][12] and also because accurate empirical interatomic potentials are readily available. [13][14][15] Vacancy aggregation is also often assumed to be a prototypical "on-lattice system," an assumption that we show here to be invalid, particularly at elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that voids, especially those locate in the near-surface region of wafers, can deteriorate gate oxide integration (GOI) and enhance the leakage current of metal-oxide-semiconductor devices (Huth et al, 2000;Park et al, 2000). As a result of the agglomerations of excess vacancies during crystal growth, it is believed that voids are normally of an octahedral structure, about 100-300 nm in size and with a thin oxide film of about 2nm on their {111} surfaces (Itsumi et al, 1995;Yamagishi et al, 1992). It has been reported that during cooling-down process of silicon crystal from the melting point to room temperature, grown-in voids are formed with densities between 10 5 -10 7 cm -3 (Yamagishi et al, 1992).…”
Section: Void Defectsmentioning
confidence: 99%